1977
DOI: 10.2307/3279573
|View full text |Cite
|
Sign up to set email alerts
|

A Lipogenic Effect in Intact Male Hamsters Infected with Plerocercoids of the Tapeworm, Spirometra mansonoides

Abstract: Plerocercoids of the tapeworm, Spirometra mansonoides, produce a potent growth stimulating substance which is active in several species of mammals. While most of the actions of the plerocercoid growth factor (PGF) are similar to those of growth hormone (GH), lipid metabolism is one area where their actions are not alike. This report demonstrates that plerocercoid infection not only stimulates growth of intact male hamsters but is lipogenic as well. The lipogenic effects of plerocercoid infection were demonstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

1982
1982
1997
1997

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…Previous work shows that plerocercoid infection stimulates growth and increases fat stores in the absence of the pituitary (STEELMAN et al, 1971) and in the absence of normal insulin levels (PHARES & CARROLL, 1978). It has also been demonstrated that plerocercoid infection causes an increase in carcass fat (MEYER et al, 1965) and increases in serum triglycerides and cholesterol (PHARES & CARROLL, 1977) of intact hamsters. There are several possible explanations of these observations.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Previous work shows that plerocercoid infection stimulates growth and increases fat stores in the absence of the pituitary (STEELMAN et al, 1971) and in the absence of normal insulin levels (PHARES & CARROLL, 1978). It has also been demonstrated that plerocercoid infection causes an increase in carcass fat (MEYER et al, 1965) and increases in serum triglycerides and cholesterol (PHARES & CARROLL, 1977) of intact hamsters. There are several possible explanations of these observations.…”
Section: Discussionmentioning
confidence: 96%
“…While GH has acute (two to three hours after exposure to hormone) effects similar to insulin in adipose tissue (BIRNBAUM & GOODMAN, 1979) the chronic effect of GH treatment is hyperglycaemia and depletion of adipose tissue stores (MERIMEE & RABIN, 1973). Unlike the effect of GH, plerocercoid infection increases fat stores (STEELMAN et al, 1971;PHARES & CARROLL, 1977;PHARES & CARROLL, 1978).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, RANDLE et al (1964) showed that perfusion of rat hearts with fatty acids or ketones inhibited glycolysis and stimulated net synthesis of glycogen. In light of the lipogenic effect of plerocercoid infection (STEELMAN et al, 1971;PHARES & CARROLL, 1977;, it is not surprising that PGF did not increase cardiac muscle glycogen from fasted rats.…”
Section: Discussionmentioning
confidence: 99%
“…However, not all of the biological actions of plerocercoid growth factor (PGF) are similar to those reported for growth hormone (GH) HARLOW et ai (1967) reported insulin-like activity in extracts of plerocercoids in vitro. In addition, a distinct lipogenic effect of plerocercoid infection was reported in hypophysectomized (Hx) rats (STEELMAN et a!., 1971), Hx-diabetic rats (PHARES & CARROLL, 1978) and intact hamsters (PHARES & CARROLL, 1977). This chronic lipogenic effect of PGF is "insulin-like" as opposed to the lipolytic effect of chronic administration of GH (KNOBIL & HOTCHKISS, 1964).…”
Section: Ntroductionmentioning
confidence: 99%
“…Growth hormone stimulates lean body growth whereas PGF stimulates growth with fattening ( 1 , 13,14). Growth hormone stimulates lean body growth whereas PGF stimulates growth with fattening ( 1 , 13,14).…”
mentioning
confidence: 99%